2021
DOI: 10.48550/arxiv.2103.09819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global Electroweak Symmetric Vacuum

Yang Bai,
Seung J. Lee,
Minho Son
et al.

Abstract: Although the Higgs potential in the Standard Model (SM) contains only a simple electroweak symmetry breaking vacuum in the small field region, additional metastable or global vacua could exist in models beyond the SM. In this paper, we study one intriguing scenario with an additional electroweak symmetric vacuum that could be the global one. For the thermal universe ending at the current metastable vacuum, the electroweak symmetry should stay non-restored at high temperatures. We realize the scenario in a mode… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…We have first studied the phenomenon of EW symmetry non-restoration, which has recently regained attention in the literature [34][35][36]99]. We have shown that in the N2HDM this behaviour is driven by contributions from the resummation of daisy diagrams.…”
Section: Discussionmentioning
confidence: 99%
“…We have first studied the phenomenon of EW symmetry non-restoration, which has recently regained attention in the literature [34][35][36]99]. We have shown that in the N2HDM this behaviour is driven by contributions from the resummation of daisy diagrams.…”
Section: Discussionmentioning
confidence: 99%
“…We have first studied the phenomenon of EW symmetry non-restoration, which has recently regained attention in the literature [34][35][36]94]. We have shown that in the N2HDM this behaviour is driven by contributions from the resummation of daisy diagrams.…”
Section: Discussionmentioning
confidence: 99%
“…The general concept of symmetry non-restoration (SNR) was first explored by Weinberg [1] and then expanded upon in [2][3][4][5][6][7][8][9][10][11][12][13]. Recently, scenarios of SNR for the electroweak sector, and the associated phenomenological observables, have become a topic of investigation [14][15][16][17][18][19][20][21]. Electroweak SNR is of special interest in the context of certain baryogenesis scenarios [22].…”
Section: Introductionmentioning
confidence: 99%